Comparison of key performance indicators between portuguese Olympic and Paralympic judo athletes - Monteiro, L.; Machado, J.; Lanham, S. N.; Langford, E. L.; Abel, M. G. (The Arts and Sciences of Judo, 2022)
The aim of this study was to compare the physical fitness and sport specific skills of blind vs. norm visual judo athletes. Twelve athletes from the Portuguese judo men's team, six from the Paralympic team (mean ± SD; Age: 28.5 ± 5.4 yr., Body mass: 69.0 ± 5.5 kg; Height: 1.73 ± 0.06 m) and six from the Olympic team (Age: 25.7 ± 3.2 yr., Body mass: 70.7 ± 6.6 kg, Height: 1.72 ± 0.06 m). Power and rate force development (RFD) were assessed in bench press, row and squat exercises and with a vertical jump. Strength was assessed via isometric handgrip strength. Shoulder and lower body flexibility were assessed with a tape and one baseline sit & reach testing box. Cardiorespiratory fitness (VO2máx) was assessed using a treadmill. The "Special Judo Fitness Test" (SJFT) was used to evaluate sport specific skills. Body composition was measured via skinfolds. Performance outcomes were compared between groups with Mann Whitney U tests The level of significance was set a p<0.05. Handgrip strength, maximal strength, bench press strength and power and SJFT were greater in the normal vision group (p<0.05). There were no group differences between blind and norm visual athletes in VO2máx, flexibility, and lower body RFD in vertical jump and squat assessments. In conclusion, upper body strength and power and technical-tactical performance outcomes were lesser among visually impaired athletes, with no difference in aerobic capacity, flexibility, and lower body power parameters. These findings identify key bio motor abilities that may be targeted in an exercise program for blind judo athletes.